The painted queen - Peters, Elizabeth, 1927-2013; Hess, Joan (Peters, Elizabeth, 1927-2013. Amelia Peabody series., 2017)
"Egypt, 1912. Amelia Peabody and her dashing archeologist husband, Radcliffe Emerson, are once again in danger as they search for a priceless, stolen bust of legendary Queen Nefertiti and Amelia finds herself the target of assassins in this long-awaited, eagerly anticipated final installment of Elizabeth Peters's bestselling, beloved mystery series"--